Respuesta :

Answer:

[tex]1. (5 \times 10^3) \times (9 \times 10^7)  = 45 \times 10^{10}\\2. (7 \times 10^5) \div (2 \times 10^2)  = 3.5 \times 10^3[/tex]

Step-by-step explanation:

Here, the given expressions are:

[tex]1. (5 \times 10^3) \times (9 \times 10^7)\\2. (7 \times 10^5) \div (2 \times 10^2)[/tex]

Now, the LAWS OF EXPONENTS state that:

[tex]1. a^ m \times a^n = a^{(m+n)}\\ 2. a^m \div a^n = a ^{(m-n)}[/tex]

Using above laws, we get:

[tex]1. (5 \times 10^3) \times (9 \times 10^7)\\= (5  \times 9 ) \times ( 10^7\times 10^3)\\= 45 \times (10^{(7+3)})  = 45 \times 10^{10}\\\implies (5 \times 10^3) \times (9 \times 10^7)  = 45 \times 10^{10}[/tex]

[tex]2. (7 \times 10^5) \div (2 \times 10^2)\\= \frac{(7 \times 10^5)}{(2 \times 10^2)}  = \frac{7}{2}  \times\frac{10^5}{10^2}   \\ =3.5 \times 10^{(5-2)}  = 3.5 \times 10^3\\\implies(7 \times 10^5) \div (2 \times 10^2)  = 3.5 \times 10^3[/tex]